Rare pulmonary barotrauma after explosive decompression: a case report - Tlapák, Jakub; Oniščenko, Boris; Došel, Petr; Požár, Pavel; Chmátal, Petr; Hájek, Michal (BMC pulmonary medicine, 2020)
BACKGROUND: Pneumothorax as a consequence of pulmonary barotrauma during explosive decompression military crew training in a hypobaric chamber is an extremely rare and sparsely diagnosed complication. Extensive bilateral tissue damage is even more unexpected. CASE PRESENTATION: A 26-year-old active duty Air Force pilot was performing an explosive decompression simulation from 8000 ft. (2438.4 m) to 25,000 ft. (7620 m) in a 1.5 s interval. The training was interrupted due to the pilot's apparent health complications. After transfer to the emergency department, a CT scan showed bilateral lung barotrauma with emphysema. CONCLUSIONS: The case report shows extensive emphysema and pneumothorax after a rapid decompression done for training purposes. It is a possible but rare complication. The cause remains unclear, with suspicion of a predisposed lung disease.
Keywords: dospělí; Decompression, Explosive; Tomography, X-Ray Computed; dekomprese explozivní; Humans; pneumotorax; Pulmonary Emphysema; plicní emfyzém; Lung Injury; poškození plic; mužské pohlaví; Adult; Case report; Pulmonary barotrauma; lidé; počítačová rentgenová tomografie; Pneumothorax; Barotrauma; Male; barotrauma; Explosive decompression